2016
DOI: 10.1177/0333102416644745
|View full text |Cite
|
Sign up to set email alerts
|

Delayed absorption of many (paracetamol, aspirin, other NSAIDs and zolmitriptan) but not all (sumatriptan, rizatriptan) drugs during migraine attacks and most likely normal gastric emptying outside attacks. A review

Abstract: Background In most pharmacokinetic studies, the oral absorption of drugs is impaired during migraine attacks but exceptions occur. A study on gastric emptying using gastric scintigraphy indicated that gastric stasis also occurs interictally in migraine. These studies were reviewed critically. Results In seven studies, mainly investigating NSAIDs and analgesics, the early absorption of the drugs during 112 migraine attacks was delayed. The absorption of sumatriptan is usual in therapeutic doses, and rizatriptan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 58 publications
(211 reference statements)
0
6
0
Order By: Relevance
“…As additional publications appeared reporting the effectiveness of oral sumatriptan in relieving migraine headache, it became increasingly apparent that the drug's administration route played an appreciable role in determining its success in relieving migraine headache attacks. Some quite good-quality studies showed that self-administered oral sumatriptan was little or no more effective than orally administered acetylsalicylic acid taken in sufficient dosage early in the course of migraine headache [29][30][31][32]. As other triptan derivatives became available for oral administration, their efficacies proved reasonably similar to that of sumatriptan.…”
Section: Agents Acting At 5-ht 1b/1d Receptorsmentioning
confidence: 99%
See 1 more Smart Citation
“…As additional publications appeared reporting the effectiveness of oral sumatriptan in relieving migraine headache, it became increasingly apparent that the drug's administration route played an appreciable role in determining its success in relieving migraine headache attacks. Some quite good-quality studies showed that self-administered oral sumatriptan was little or no more effective than orally administered acetylsalicylic acid taken in sufficient dosage early in the course of migraine headache [29][30][31][32]. As other triptan derivatives became available for oral administration, their efficacies proved reasonably similar to that of sumatriptan.…”
Section: Agents Acting At 5-ht 1b/1d Receptorsmentioning
confidence: 99%
“…Such contingencies are likely to slow the rate and perhaps decrease the completeness of the absorption of swallowed drugs unpredictably even before pre-systemic metabolism may come into play. Tfelt-Hansen's [30] review of the issue noted the existence of published data suggesting that the early absorptions of sumatriptan and rizatriptan were not delayed during migraine attacks though the time of reaching the peak circulating concentration of the former was. There was evidence of interference in the absorptions of the other triptans during headache.…”
Section: Agents Acting At 5-ht 1b/1d Receptorsmentioning
confidence: 99%
“…See Table 6 for suggested doses. For concomitant nausea, simple analgesics may be combined with antiemetics to treat the nausea, but there is no conclusive evidence that antiemetics improve the absorption of common analgesics [11]. Metoclopramide tablet 10 mg or tablet domperidone 10 mg can be used (the latter used especially for young people due to less risk of extrapyramidal side effects).…”
Section: Simple Analgesics and Antiemeticsmentioning
confidence: 99%
“…24 Consequently, metoclopramide has been incorporated into numerous guidelines as it may be beneficial in reducing nausea while enhancing the efficacy of concurrent analgesics. 1,25 Dopamine antagonists such as prochlorperazine or chlorpromazine are effective in controlling nausea and vomiting. 26 Data are lacking on the efficacy of serotonin antagonists in migraine.…”
Section: Migraine-relatedmentioning
confidence: 99%